HUBUNGAN SENSE OF BELONGING DENGAN PARTISIPASI MASYARAKAT PADA BANK SAMPAH DI WILAYAH KECAMATAN KEMAYORAN - Amalia, Atika Fiqih; Purwandari, Dian Alfia; Yuliani, Shahibah (Edukasi IPS, 2020)
This objective of this study is to find the relationship of sense of belonging with community participation in waste banks in the Kemayoran District Area. This research was conducted with a quantitative approach. The population of this study was 134 residents who participated in the waste bank in the Kemayoran District Area. This research sampel is 100 residents who are administrator and customers the Waste Banks. Data analysis uses simple linear regression analysis test of correlation. The research releaved that there was a correlation beetwen sense of belonging and society participation in the waste banks seen from the calculation of the correlation between variables that is equal to r = 0,373 and the effective contribution of sense of belonging with society participation in the waste bank was 13,9% (r2 =0,139%). The results of these calculations indicate that the sense of belonging as a factor of participation is behind 13.9%. There other factors that influence the sense of belonging such as trust, the similarities that belong to organization members, age, social interaction and family functions which can motivate public participation in the garbage bank in the Kemayoran District Area by 86.1%. This research can be used as a reference for further research in the field of social and environmental sciences